2021
DOI: 10.3389/fchem.2021.664602
|View full text |Cite
|
Sign up to set email alerts
|

Sinapic Acid and Sinapate Esters in Brassica: Innate Accumulation, Biosynthesis, Accessibility via Chemical Synthesis or Recovery From Biomass, and Biological Activities

Abstract: Sinapic acid (SinA) and corresponding esters are secondary metabolites abundantly found in plants of Brassica family. Belonging to the family of p-hydroxycinnamic acids, SinA and its esters analogues are present in different plant parts and involved in multiple biological processes in planta. Moreover, these metabolites are also found in relatively large quantities in agro-industrial wastes. Nowadays, these metabolites are increasingly drawing attention due to their bioactivities which include antioxidant, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 111 publications
(169 reference statements)
0
37
0
1
Order By: Relevance
“…'Rambo'), white mustard (Sinapis alba L.), and red cabbage (Brassica rapa L., var. capitata) are rich in two major groups of phenolic compounds: glycosylated flavonols and hydroxycinnamic acid derivatives (mainly represented by kaempferol and sinapic acid derivatives) [5,6]. These compounds have been associated with radical scavenging activities at the intracellular level, eliminating reactive oxygen species (ROS) and thus preventing deleterious effects associated with oxidative stress [7].…”
Section: Introductionmentioning
confidence: 99%
“…'Rambo'), white mustard (Sinapis alba L.), and red cabbage (Brassica rapa L., var. capitata) are rich in two major groups of phenolic compounds: glycosylated flavonols and hydroxycinnamic acid derivatives (mainly represented by kaempferol and sinapic acid derivatives) [5,6]. These compounds have been associated with radical scavenging activities at the intracellular level, eliminating reactive oxygen species (ROS) and thus preventing deleterious effects associated with oxidative stress [7].…”
Section: Introductionmentioning
confidence: 99%
“…Sinapic acid may be found in free form or esterified like other HCAs. These esters can be sugar conjugates (glycosides) such as sinapoyl glucose (identified in this study), or conjugates of other compounds, such as sinapoyl malate (identified in this study) and sinapoyl choline or sinapine (a source of sinapic acid and choline in germinating mustard seed) [ 39 , 40 , 41 , 42 ]. Tinte et al [ 11 ] also identified sinapic acid, sinapoyl glucose and sinapoyl malate in Arabidopsis after treatment with LPS from B. cepacia Furthermore, the antibacterial activity of sinapic acid against both Gram-positive and Gram-negative bacteria have been reported in mustard seeds [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The available experience demonstrated the capacity of this material to induce anti-cancer, anti-inflammatory, and/or modulatory effects on metabolic processes in different cell systems [ 5 , 10 , 11 , 12 ], focusing the attention on the organosulfur biocomponents to drive the fine-tuning of the processing methods [ 13 ]. The health-promoting activity is commonly ascribed, not only to a single compound, but also to a group of bioactive phytochemicals in the food matrix (e.g., kaempferol glycosides or hydroxycinnamic acid derivatives [ 14 , 15 ]) that may contribute to the capacity to scavenge reactive oxygen species (ROS) and, thus, reducing oxidative stress and mutagenic events [ 16 ]. Indeed, both types of compounds (organosulfur and phenolics) provide complementary bioactivities that boost the final health benefits of cruciferous foods [ 17 ].…”
Section: Introductionmentioning
confidence: 99%